Cultural Adaptation of the Three Good Things Protocol for Drug Abusers Undergoing Drug Rehabilitation - Leni Nurul Azizah; Asteria D. Kumalasari; Efi Fitriana (Dinasti Publisher, 2025)
In 2021, the prevalence rate of drug abusers in Indonesia reached 3.66 million. This is concerning because a number of residents will experience a decrease in productivity. Meanwhile, existing interventions have not prevented relapse. This study aims to adapt the Three Good Things Protocol as a supplementary approach for drug users during rehabilitation. The cultural adaptation methods are based on Barrera and Castro (2013) and consist of three stages: (1) gathering information, studying literature (31 sources), and conducting interviews with five counselors and stakeholders; (2) designing a preliminary adaptation with the help of two translators, linguists, and psychologists; and (3) testing the preliminary adaptation through a 14-day pilot study, participants (n = 4), and consulting with two psychologists and one counselor. Fourth, adaptation refinement involves improving the protocol based on feedback results. The evaluation of protocol acceptance uses the TFA interview guidelines (Sekhon, 2017). The results showed several modifications from the original protocol to the Indonesian version, including aspects related to participant characteristics, media, reminders, and emotional expression space. The level of acceptance from experts and participants was acceptable. Participants showed an increasing trend of positive affect and a decreasing trend of negative affect on days 1, 7, and 14, but these results still need to be tested for effectiveness. In conclusion, this study produced an Indonesian version of the Three Good Things Protocol that is culturally appropriate and acceptable with various adjustments.